2013
DOI: 10.1152/japplphysiol.00707.2012
|View full text |Cite
|
Sign up to set email alerts
|

Central common drive to antagonistic ankle muscles in relation to short-term cocontraction training in nondancers and professional ballet dancers

Abstract: Optimization of cocontraction of antagonistic muscles around the ankle joint has been shown to involve plastic changes in spinal and cortical neural circuitries. Such changes may explain the ability of elite ballet dancers to maintain a steady balance during various ballet postures. Here we investigated whether short-term cocontraction training in ballet dancers and nondancers leads to changes in the coupling between antagonistic ankle motor units. Eleven ballet dancers and 10 nondancers were recruited for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In general, the mechanisms of controlling antagonistic muscle activity during an action of an agonistic muscle include the inhibition of spinal α-motoneurons of the antagonist by reciprocal Ia inhibitory interneurons and the supraspinally mediated depression of afferent feedback by presynaptic inhibition during most movements. These mechanisms are controlled by supraspinal centers (Crone and Nielsen 1989;Nielsen 2004;Geertsen et al 2013). Although the exercises during balance training require simultaneous and alternating activity of antagonistic muscle groups (Nielsen and Kagamihara 1992;Nielsen et al 1994), our results indicate that the training regimen decreases co-activity of TA at the onset of contraction during an isometric MVC of the plantar flexors.…”
Section: Discussionmentioning
confidence: 67%
“…In general, the mechanisms of controlling antagonistic muscle activity during an action of an agonistic muscle include the inhibition of spinal α-motoneurons of the antagonist by reciprocal Ia inhibitory interneurons and the supraspinally mediated depression of afferent feedback by presynaptic inhibition during most movements. These mechanisms are controlled by supraspinal centers (Crone and Nielsen 1989;Nielsen 2004;Geertsen et al 2013). Although the exercises during balance training require simultaneous and alternating activity of antagonistic muscle groups (Nielsen and Kagamihara 1992;Nielsen et al 1994), our results indicate that the training regimen decreases co-activity of TA at the onset of contraction during an isometric MVC of the plantar flexors.…”
Section: Discussionmentioning
confidence: 67%
“…; Geertsen et al. ). Similar to this study, changes in coherence have been observed with improvements in motor performance (Perez et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Geertsen et al. ), but disappear again within minutes following a single training bout, despite maintained motor performance abilities. In this study, we did not obtain a second delayed measure of coherence following motor practice, as the test was very time consuming and involved considerable mental and physical effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-contraction around the ankle joint occurs during tasks such as standing on one leg, balancing on an unstable platform or reacting to rotation of a support surface, or walking on a narrow beam (Diener et al, 1983; Keshner et al, 1987; Nielsen and Kagamihara, 1992; Geertsen et al, 2013) or after fatigue (Kennedy et al, 2012). However, co-contraction is not a rule under different critical postures (Sozzi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%